ANALISIS POTENSI UBI KAYU DALAM RANGKA KETAHANAN PANGAN DI KABUPATEN WONOGIRI - Tabri Karyanto; Son Suwasono (BUANA SAINS, 2008)
Farming of cassava has been recognized to be one of important farming in Wonogiri. However, development of such farming runs slowly as there are still many farmers implementing traditional farming technologies. The aims of this research were to: (1) study of the potency of production and food availability of cassava in the frame-work of food security; (2) study of farming enterprises system. Research location was purposively determined based on potency of cassava. Research location covered Wuryantoro, Ngadirojo and Sidoharjo districts. Results of the research indicated that food availability was equal to 7.124.43 calorie /capita/day. The land area significantly influenced cassava productivity. The farming enterprises can make profit 49.01%. B/C ratio was 1.51. LQ of cassava was equal to 3,370 (LQ > 1)